An adverse lipid profile and increased levels of adiposity significantly predict clinical course after a first demyelinating event. Issue 5 (20th March 2017) - Tettey, Prudence; Simpson, Steve; Taylor, Bruce; Ponsonby, Anne-Louise; Lucas, Robyn M; Dwyer, Terence; Kostner, Karam; ,; van der Mei, Ingrid AF
Abstract : Objective: To investigate the prospective associations between adiposity and lipid-related variables and conversion to multiple sclerosis (MS), time to subsequent relapse and progression in disability. Methods: A cohort of 279 participants with a first clinical diagnosis of central nervous system demyelination was prospectively followed to 5-year review. Height, weight, waist and hip circumference were measured, and serum samples taken for measurement of lipids and apolipoproteins. Survival analysis was used for conversion to MS and time to relapse, and linear regression for annualised change in disability (Expanded Disability Status Scale). Results: Higher body mass index (BMI; adjusted HR (aHR): 1.22 (1.04 to 1.44) per 5 kg/m 2 increase), hip circumference (aHR: 1.32 (1.12 to 1.56) per 10 cm increase) and triglyceride levels (aHR: 1.20 (1.03 to 1.40) per unit increase) were associated with increased risk of subsequent relapse, while adiposity and lipid-related measures were not associated with conversion to MS. In addition, higher BMI (β: 0.04 (0.01 to 0.07) per 5 kg/m 2 increase), hip circumference (β: 0.04 (0.02 to 0.08) per 10 cm increase), waist circumference (β: 0.04 (0.02 to 0.07) per 10 cm increase), total cholesterol to high-density lipoprotein ratio (TC/HDL ratio; β: 0.05 (0.001 to 0.10) and non-HDL; β: 0.04 (0.001 to 0.08) at study entry) were associated with a higher subsequent annual change in disability. Conclusions: Higher levels of adiposity, non-HDL and TC/HDL ratio were prospectively associated with a higher rate of disability progression, and higher adiposity and triglycerides were associated with relapse but not with conversion to MS. Improving the lipid profile and losing weight into the healthy range could reduce the accumulation of disability.